Pengaruh Strategi Inovasi Terhadap Penggunaan Teknologi Informasi Dalam Industri UMKM - Sendy Pratama; Thara Yuniar; Wishal Putra Hendrawan; Indah Noviyanti (Jurnal Bintang Manajemen, 2024)
In the current era of digitalization and globalization, innovation strategies are very important to build MSMEs to improve performance and competitiveness. The aim of this research is to understand the impact of innovation strategies on the use of information technology in the Micro, Small and Medium Enterprises (MSME) sector in Indonesia. This research applies a qualitative approach to analyze data from various relevant literature, such as books and scientific journals, to understand how innovation strategies can encourage the adoption of information technology and how this technology contributes to improving the performance of MSMEs. This research shows that the synergy between innovation strategies and the use of information technology is very useful for improving the performance and competitiveness of MSMEs. By using innovation strategies and utilizing information technology effectively, MSMEs can overcome various business challenges and take advantage of market opportunities to achieve sustainable growth and long-term success. The results of this research provide a significant contribution to understanding and practice in the MSME industry.